Critical Leadership Competencies and Styles of Effective Leaders of the Sustainability Agenda in Businesses - Sen, Manojit (Global journal of Business and Integral Security, 2025)
Purpose: One of the biggest challenges of our time is that of climate change. While offering the much-needed goods and services to society, businesses collectively have also contributed significantly to climate change. Business leaders need to play an active role in addressing this via a bespoke Sustainability Agenda, a set of actions big or small depending on the organization’s carbon footprint, to get to Net Zero. In a field which is riddled with complexity, this study is an effort to understand which leadership attributes enable leaders to be effective in driving the Sustainability Agenda. This research studies the combination of four critical Leadership Competencies and three Leadership Styles that leaders need to possess, to drive this agenda successfully. Methods: This research shortlists the most critical leadership competencies and styles for leaders driving the Sustainability Agenda. It uses a 25-question survey to ascertain perceptions of employees in businesses globally on leaders who are perceived to be effective in driving the Sustainability Agenda and their distinguishing attributes. This research also explores the role of Organizational Culture in enabling the leader’s effectiveness. Results: The vast majority of survey respondents perceive that the most effective leaders driving the Sustainability Agenda demonstrate the Transformational Leadership style and/or Transactional Leadership Style combined with the key leadership competencies of Transformational, Ethical, Strategic and Team Leadership. Less than half respondents perceive leaders with the Passive-Avoidant style as effective. 90% of respondents perceive the six dimensions of organisational culture selected to be very important in enabling business leaders’ effectiveness in driving the Sustainability Agenda. Conclusion: With today’s challenge of climate change, effective business leadership of the Sustainability Agenda is key. Recruitment and development of business leaders to lead the Sustainability Agenda will bear significant results if it can focus on the combination of four critical Leadership competencies and Transformational and/or Transactional styles of leadership. Furthermore, organisations have to embed certain key aspects of organizational culture to enable leaders to be effective in successfully driving the Sustainability Agenda.